Kemampuan Laba Untuk Memprediksi Return Saham - Putri, Anne (Jurnal Ekonomi, 2010)
The obejective of this study is to examine the predictive content of fiskal profit. Linear regression models are developed to test the hypotheses that taxable income is useful to predict future stock return. Using a sample of 55 manufacturing firms listed in Indonesia Stock Exchange for the periode of 2002-2007, this study finds that empirical evidence supports the proposed hypotheses.